(untitled) (International Journal of Engineering and Computer Science, 2014)
Every user reminder application available in the market for mobile phones is time and date based. Also, the user has to make a manual typed entry for setting up a reminder. On the reminder being ON, the device constantly tries to match the device time and date with the saved reminder time and date, and the user will be alerted by a text pop up and an optional sound frequency alarm if it is a match. But while setting up many reminders the user will not be aware about the time and date, but he will be aware about the location where he wants the reminder. Some reminders are location personified rather than a particular date or time. In this project which would be a vast and very useful application, we have tried to design an application which helps the user in setting up easy reminders by using voice commands and which gives alerts about the reminder when he enters into the geographical sector specified in the reminder by the user.